Menyelamatkan dan Potensi Penyelamatan Ekonomi Pasca Covid-19: : Adopsi Kebijakan Literasi Digital untuk Sektor UMKM - Purwanto Putra (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2022)
Almost all countries in the world are facing the Covid-19 pandemic whose spread is so massive. This affects various aspects of human life and has a domino effect in various fields including the economy. Indonesia's economy worsened, recorded in the second quarter (Q2) of 2020 experiencing a contraction of 5.32 percent. The UMKM sector has a strategic role and is predicted to be the motor for economic recovery after the Covid-19 pandemic. This can be seen from the trend of the positive contribution of MSMEs to Indonesia's GDP in the pre-pandemic period which increased by around 60%. However, in this uncertain condition, ideas and innovations are needed in order to get out of the pressures and the worst possible economic crisis. This research will look at the potential for adopting digital literacy skills in the MSME sector as a strategy for post-Covid-19 economic recovery. This study uses a qualitative-descriptive approach with the application of the information literacy method, The Big 6. The application of this method is expected to be a way to build more detailed and in-depth arguments regarding the subject of research. The results showed that the idea of adopting MSME digital literacy skills was needed as an answer to the challenges regarding the possibility of innovative behavior change (behavior) in the post-Covid-19 field of MSME. The transformation of MSMEs in the field of digital literacy in all sectors (production, promotion and marketing) has the potential to support faster post-Covid-19 economic recovery.